Open Space Pattern of Kotagede Settlement - Bangun IR Harsritanto; Bambang Setioko; Mustika Kusumaning Wardhani (Journal of Architectural Design and Urbanism, 2018)
Yogyakarta is a city with high urban development and rapid urbanisation stream. Those phenomena affected the dwelling process in urban-rural settlement in Kotagede heritage area. Previously Kotagede is old capitol city of Mataram with Keraton characters and organic traditional settlement. However recent developments showed transformation in Kotagede open public space. Some factors such internal and external might be involved in the transformation. This study aimed brief explanations about open space pattern in heritage area of Kotagede Yogyakarta using qualitative and quantitative methods in demand. The research object is the public open space in Kotagede. The methods are quantitative and qualitative in demands with deductive analysis in rationalistic frame. The Deductive used in analyzing the identification results with the several theories to explain the phenomenon. The quantitative method will be used to simplify the initial procedure of transformation factors. The qualitative method will be used to enhance the factors power and relate with the pattern changes. The results showed that internal and external factors bring impact to the open space pattern in Kotagede and the patterns of open space were transformed in demands. The findings give warning to the further development of Kotagede settlements